Slovenščina z ruskim naglasom - Makarova, Irina (Jezik in slovstvo, 2020)
The article offers a preview and a linguistic evaluation of the most typical errors identified in Slovenian speech production of Russian-speaking migrants. The study is based on a transcription of interviews with ten informants, mostly beginner speakers of Slovenian, focusing on problem-solving mechanisms in L2 communication in two related Slavic languages. The research is theoretically based on concepts used primarily in contemporary Russian psycholinguistics (Tsejtlin, Gagarina, Dobrova, Jelisejeva, Polinskaja, Vojejkova, Zalevskaja), dealing with the process of language acquisition in both the first and the second language.
Keywords: analiza jezikovnih napak; interlanguage; language acquisition; language error analysis; Russian; ruščina; Slovenian for foreigners; Slovenian language; slovenščina; slovenščina za tujce; usvajanje jezika; vmesni jezik